The attitude of kidney transplant recipients towards elective arteriovenous fistula ligation - Bardowska, Klaudia; Letachowicz, Krzysztof; Kamińska, Dorota; Kusztal, Mariusz; Gołębiowski, Tomasz; Królicki, Tomasz; Zajdel, Karolina; Mazanowska, Oktawia; Janczak, Dariusz; Krajewska, Magdalena (PloS one, 2020)
Arteriovenous fistulas (AVF) are a source of various complications. Among previously hemodialyzed kidney transplant recipients (KTxR), the AVF may persist over time. The patients' decisions whether to ligate the functioning AVF may be prompted by many factors. Our knowledge of benefits concerning the procedure as well as patients' attitude towards it is scarce. An anonymous survey was carried out among 301 previously hemodialyzed KTxR. The patients were recruited during scheduled visits in the Transplantation Outpatient Unit. All subjects completed an anonymous questionnaire including questions about their attitude towards the matter in question. 69 patients (22.9%) have considered AVF closure. The most common causes for such attitude were esthetic reasons (n = 29) and concerns about heart health (n = 13). Among those 69 subjects, 18 have presented with symptomatic AVF due to multiple symptoms. Symptomatic AVFs were localized on the forearm in 14 out of 18 cases. As many as 116 (38.5%) cases have never wanted to ligate the AVF and 116 (38.5%) subjects did not have a clear opinion. In our study we report 158 (52.5%) cases of non-functioning AVFs. The main reason for the above was spontaneous AVF thrombosis (121 cases). Only 24 subjects reported to rely on the physician-provided information about the AVF management. One fourth of KTRs have ever considered AVF ligation. There is a distinct need for educating patients on the possibilities of post-transplantation AVF management.